Optimizing Supplier Selection: A Comparative Study of Fuzzy VIKOR and Fuzzy Moora for Performance-Based Decision Making - Johan Krisnanto Runtuk; Steven Christanto; Poh Kiat Ng (IEEE Access)
Supplier selection is crucial in supply chain management, directly impacting operational efficiency and production continuity. This study compares two Multi-Criteria Decision Making (MCDM) techniques—Fuzzy VIekriterijumsko KOmpromisno Rangiranje (VIKOR) and Fuzzy Multi-Objective Optimization based on Ratio Analysis (MOORA)—to optimize supplier selection for a manufacturing company in Indonesia facing single supplier dependency. Fuzzy logic is employed to reduce subjectivity and ambiguity in the selection process. The Fuzzy MOORA method achieved a sensitivity score of 16.7% compared to 0.00% for Fuzzy VIKOR, indicating higher responsiveness to changes in criteria weights. Additionally, Fuzzy MOORA reduced the supplier selection process time by 28.5% compared to the current system, demonstrating its efficiency in practical applications. In general, the Fuzzy MOORA is superior in terms of the performance level with a rate of 3 out of 4 factors including the computational times, simplicity, and mathematical calculation. This study contributes to enhancing supplier selection methodologies by providing a comparative analysis of these techniques in a real-world context.